Deep Learning Method for Bearing Fault Diagnosis - LIU Xiu; MA Shan-tao; XIE Yi-ning; HE Yong-jun (Journal of Harbin University of Science and Technology)
In recent years, deep learning technology has shown great potential in bearing fault diagnosis based on vibration signals.However, in the fault diagnosis method based on deep learning, the traditional single network topology feature extraction has weak discrimination and low noise robustness, and the accuracy of fault diagnosis is not high.In addition, most of the current research methods have a low fault recognition rate in a variable load environment.In response to the above problems, this paper proposes an improved neural network end-to-end fault diagnosis model.The model combines convolutional neural networks (CNN) and the attention long short-term memory (ALSTM) based on the attention mechanism, and uses ALSTM to capture long-distance correlations in time series data , Effectively suppress the high frequency noise in the input signal.At the same time, a multi-scale and attention mechanism is introduced to broaden the range of the convolution kernel to capture high and low frequency features, and highlight the key features of the fault. After testing on multiple data sets, and comparing with existing methods, experiments show that the method in this paper has significant performance in accuracy, noise robustness, and fault recognition rate under variable load conditions.